Analisis Sistem Antrian dengan Model M/M/1 dan Model M/M/S (Studi Kasus : Seblak Mamah Saleh Cabang 2 Bandung) - Wulandari Nur Fitri; Rainnada Shalma; Indri Ratna Ayu; Somadi Somadi (Indo Publishing, 2026)
High public demand for Seblak Mamah Saleh (Bandung Branch 2) results in long queues at certain times, negatively impacting customer satisfaction and operational efficiency. This study aims to analyze the characteristics and performance of the queuing system at this location. The research employs queuing theory, specifically the M/M/1 and M/M/S models. Analysis using the M/M/1 model revealed a system utilization value of 1.93, indicating an unstable system where the queue grows indefinitely. To address this, the number of cashiers was increased from one to two. The M/M/S model analysis showed that system utilization dropped to 0.963, with a 0.02 probability of the system being empty. Additionally, the average number of customers in the system was 26.82 (with 24.90 in the queue), the average time spent in the system was 20.37 minutes (with 18.91 minutes spent waiting in the queue), and the probability of a customer having to wait was 94.5%. Although the probability of waiting remains relatively high, the addition of a cashier successfully stabilized the queuing system